Math, asked by venkataramana966677, 1 year ago

If p(x) = 2x3 – 5x2 + 4x – 1 then find p(-)

Answers

Answered by tanishameena41
0

5/-4

Step-by-step explanation:

p{x} = 2×3 -5×2 +4x-1

0 =6-10+4x-1

0= -4-1-4x

0 = -5-4x

5 = -4x

5/-4 = x

Answered by Devdatta2004
1

Answer:

-1,5/2,1/4

Step-by-step explanation:

2x3 - 5x2 +4x -1

x^2 ( 2x - 5) 1 (4x - 1)

(x^2 + 1) (2x-5) (4x-1)

x = - 1

x = 5/2

x = 1/4

It is a cubic equation... So it has 3 zeroes

Hope it helps...

Plz... Mark as branliest

Similar questions